PENINGKATAN HASIL BELAJAR SENI BUDAYA MELALUI IMPLEMENTASI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) - ., Aminah Usman (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research was carried out aimed at improving student learning outcomes in the Cultural Arts subject in unisono singing material through the application of the Contextual Teaching and Learning (CTL) approach in class VII-I of Peureulak 1 Junior High School in semester I of the 2017-2018 academic year. This research is a Classroom Action Research (CAR) carried out in two cycles, in each cycle using several research procedures including, planning, implementing, observing and reflecting. Data collection techniques used in research through tests of student learning outcomes are used to determine student learning completeness after an action. The research subjects were students of class VII-I, amounting to 24 students. The results showed that through the Contextual Teaching and Learning (CTL) approach, it turned out that student learning outcomes improved in each cycle. Mastery of the material at the initial condition was still very low or had not been successful. Out of 24 students, only 9 students (37.5%) achieved the Minimum Completion Criteria (KKM) which was set at 70 with an average value of 60. From the research data it was revealed that in cycle I (one) the average value of students totaled 69, mastery learning reached 62.5%, the achievement of these values ??showed an increase in the acquisition of values ??in the initial conditions. While in cycle II (two) the average value of students was 79 and mastery learning reached 92%. The conclusion of this study is the application of the Contextual Teaching and Learning (CTL) approach to the learning of Cultural Arts in singing material unisono can have a positive effect on improving student learning outcomes in class VII-I of Peureulak 1 semester in the first semester of the 2017-2018 academic year.